ЯНГИ ЎЗБЕКИСТОНДА ИНСОН ҲУҚУҚЛАРИНИ ҲИМОЯ ҚИЛИШ БЎЙИЧА ИЖТИМОИЙ ШЕРИКЛИКНИНГ ҲУҚУҚИЙ АСОСЛАРИ - Нишанбаева, Э.З. (SCIENCE and SOCIETY, 2024)
This article analyzes issues such as the legal basis of social partnership for the protection of human rights in the new Uzbekistan and the coverage of human rights and freedoms.
Keywords: social partnership; public control; social responsibility; rule of law; non-governmental organization; development strategy; civil society